Villgro Incubator : India Case Study - World Bank (Washington, DC, 2014)
Villgro is a business incubator with a unique rural orientation. It concerns itself not only with the launch of new businesses but more generally with the transfer of new products, knowledge, and services into rural space. Faced with the challenge of finding technologies that match rural requirements, Villgro has linked marketable product and service concepts from diverse sources with entrepreneurs who have start-up experience - so-called serial entrepreneurs. Other incubators may have difficulty imitating Villgro's business model. The conditions for its development are unique, its management approaches are relatively untested, and the values of its management team are deeply intertwined with perceptions of how the rural business system operates in India. However, other startup incubators can learn from Villgro the importance of getting management basics right before attempting to transform an entire agricultural sector. Good governance, transparency, accountability, building teams around highly capable employees, and continuously enhancing management skills are important no matter the strategic orientation of the emerging incubator.